Improvement of Deep Reading Skills and Local Cultural Metacognition Using Culturally Responsive Teaching for High School Students - Arianto Arianto; Yeti Mulyati; Yulianeta Yulianeta; Isah Cahyani (Yayasan Keluarga Guru Mandiri, 2026)
The skills of deep reading and metacognitive skills through the utilization of local culture are becoming increasingly relevant in the context of education. The analysis of the use of culturally based materials shows that this integration enhances reading skills, but also positively impacts students' metacognitive learning. This study aims to examine improvements in deep reading skills and cultural metacognition through Culturally Responsive Teaching (CRT). The quantitative experimental method uses a one-group pretest-posttest design, which provides pre-test and post-test assessments. The sample for this study consists of 13 grade-10 students at SMA Al-Amanah in Lembang, West Java, using a total sampling technique. This research proves that the culturally responsive teaching approach (CRT) is effective in enhancing students' deep reading skills and cultural metacognition. In terms of deep reading, the average score increased from 70.00 to 78.08 and the median from 65 to 80, with test results indicating statistical testing (p = 0.006) and a large effect size (Cohen's d = 0.919). Cultural metacognition, including Cultural Awareness, Reflection, Self-Regulation, and Knowledge, also improved, with total scores rising from 63.75% to 78.8%. The dimension of Cultural Knowledge showed the largest increase, at 20.9%. The findings of this research confirm that CRT not only enhances deep text comprehension abilities but also strengthens cultural metacognitive awareness and skills.